Analysis of The Implementation of Online Presence System at PT X - Salwa Alamanda Yusuf; Osly Usman; Suherdi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Practically all institutions need information about the attendance of their staff, which is crucial data for administration such as payment of salaries and incentives. Currently, in the era of globalization, the main priority is to improvise those business activities that can increase effectiveness and efficiency. Using an online-based attendance system in this situation could be the answer. The author's focus is to see how the online presence system is implemented at PT X. The aim of this research is to find out the implementation of the online-based attendance policy at PT X. The method used in this research is a qualitative method with a descriptive analysis approach and the analysis of the theory of policy implementation from George C. Edwards III. There were five informants. Data collection techniques are literature study, field study (observation and interviews) and documentation. The author uses qualitative data analysis techniques by processing data from interviews and observations to draw conclusions so that they can answer the problems in the research. The result show that PT X uses the Qantor application which is equipped with GPS technology to monitor employee locations effectively and efficiently. This application meets the four indicators of policy implementation: communication, resources, disposition, and bureaucratic structure, with the advantages of ease of use, increased discipline and productivity, and data that cannot be manipulated. However, there are shortcomings related to technical problems such as errors when logging in.